Ezetimibe Anticancer Activity via the p53/Mdm2 Pathway - Charmy Twala; Sibusiso Malindisa; Chamone Munnik; Selisha Sooklal; Monde Ntwasa (Biomedicines)
Background: Ezetimibe is used to treat cardiovascular disease as it blocks the sterol transporter Niemann-Pick C1-Like 1 (NPC1CL1) protein. However, recent evidence indicates that Ezetimibe inhibits several cancers indirectly by reducing circulating cholesterol or via specific signalling pathways. Methods and Results: Our in silico studies indicate that Ezetimibe binds to the Tp53 binding domain in Mdm2, forming a more thermodynamically stable complex than nutlin3a. Furthermore, a docking study of the newly developed inhibitors—RG7388 and RG7112—was conducted. This further showed lower binding energies of −6.337 kcal/mol and −6.222 kcal/mol, respectively, when compared to the −7.919 kcal/mol exhibited by Ezetimibe. We show that Ezetimibe inhibits the growth of several cancer cell lines at concentrations that are not toxic to a normal cell line. Conclusions: Thus, Ezetimibe is probably active against cancers that overexpress Mdm2. Moreover, inhibitors of RBBP6 may be combined with Ezetimibe for effective anticancer activity. Due to poor oral bioavailability, Ezetimibe must be administered parenterally for cancer treatment.